Plyometric weight training can increase hip and ankle joint strenth significantly - Liu, Y.; Jing, L.X.; Fu, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purposes of this study were to (1) investigate the changes in muscle strength and power at each joint of lower extremity, kinetics and stiffness of hip, knee, and ankle joints during counter-movement jump with different weights before and after plyometric weight training (PWT); (2) compare each of the joint contributions during plyometric exercises with different weights. Sixteen basketball players were asked to perform the PWT, i.e. 3 groups continued CMJ with the weight of 30% 1RM for 8-weeks with incremental-loads. Before and after the 8-week training program, kinematics and kinetics of the lower-limb were collected during CMJ performance. Joint moment, joint power, joint stiffness, and joint contirbution were then determined. The results indicated that an 8-week plyometric weight training program could significantly increase jump height, peak GRFv, and power output. The results also revealed that muscle strength and power of hip were dominantly developed during PWT and the enhanced kinetics (moment and stiffness) of hip turned out to be a major factor responsible for the improved jump performance.